Предмет: Математика,
автор: sagdianatasbolat
помогите пожалуйста срочно 100баллов даю
Приложения:
Ответы
Автор ответа:
1
Пошаговое объяснение:
2(х - 3/4) - 3(2х + 4/9 - у) + 6(х - 1/2у) =
2х - 6/4 - 6х - 12/9 + 3у + 6х - 6/2у =
2х - 1 2/4 - 6х - 1 3/9 + 3у + 6х - 3у =
(2х - 6х + 6х) + (3у - 3у) + (-1 2/4 - 1 3/9) =
2х + 0 + (-1 18/36 - 1 12/36) =
2х + (-2 30/36) = 2х - 2 30/36 = 2х - 2 5/6
sagdianatasbolat:
спс
Похожие вопросы
Предмет: Немецкий язык,
автор: ivansadovij1505
Предмет: Геометрия,
автор: evapavlenko587
Предмет: Литература,
автор: tanagnoevaa6
Предмет: Музыка,
автор: ramismamutov